STRATEGIES FOR DEVELOPING DEONTOLOGICAL CULTURE IN TEACHERS - Sharipova Go’zal (Prospects for innovative technologies in science and education, 2025)
This article explores effective strategies for enhancing deontological culture among teachers, which is essential for maintaining professional ethics, responsibility, and integrity in the field of education. A strong deontological foundation in teachers helps promote trust, fairness, and respect within the learning environment and fosters the development of moral values in students. The article highlights the importance of continuous ethical training, institutional support, and reflective practices in reinforcing deontological norms in teachers' daily professional activities. It also examines how collaboration among stakeholders—educational institutions, families, and the wider community—can contribute to the ethical development of teaching staff. Drawing on psychological and pedagogical research, the article presents both theoretical insights and practical approaches to embedding ethical conduct as a core aspect of teacher professionalism.